SOSIALISASI PENGGUNAAN APLIKASI RUANG GURU UNTUK PEMBELAJARAN DARING - Tambunan, Marlina Agkris (Jurnal Pengabdian Bukit Pengharapan, 2021)
The purpose of this community service activity is to socialize various applications used in online learning (on the network). One of these applications is the use of the teacher's room application to help students and teachers deal with learning during the pandemic. Every human being is obliged to get a proper education wherever they are and education can change the mindset for the better and positive. One form of education pattern in responding to the 4.0 industrial revolution is to use smartphones/gadgets as an educational medium called the Ruang Guru application. The teacher room application is a digital-based application that can be accessed anywhere and anytime, and its use is easy and helpful in learning problems. Ruang Guru provides a learning management system that can be used by students and teachers to manage learning activities in the classroom virtually. Equipped with thousands of question banks whose content is adjusted to the applicable curriculum in Indonesia. The method used in this activity is a varied lecture accompanied by practice. The results of this activity are the skills of teachers and students in using the teacher's room application, especially teachers of SMP Negeri 1 Hutabayuraja who have not used the application. After this socialization, the needs of teachers and students are quite answered in online learning. Keywords: socialization, teacher room application, online learning